Short-term effect of intravitreal ranibizumab on intraocular concentrations of vascular endothelial growth factor-A and pigment epithelium-derived factor in neovascular glaucoma - Wang, Jia Wei; Jonas, Jost B. (Clinical & experimental ophthalmology, 2015)
Background: This study aims to evaluate concentrations of pigment epithelium-derived factor (PEDF) and vascular endothelial growth factor (VEGF)-A in aqueous of patients with neovascular glaucoma prior to, and shortly after, an intravitreal ranibizumab injection. Design: Interventional comparative study. Participants: The study included patients undergoing an intravitreal ranibizumab injection about one week before anti-glaucomatous surgery (study group) or who underwent routine cataract surgery (control group). Methods: Aqueous and blood samples were collected at the occasions of intravitreal injections, anti-glaucomatous surgery or cataract surgery. They were analysed by enzyme-linked immunosorbent assay. Main Outcome Measures: Concentrations of PEDF and VEGF-A in aqueous. Results: At baseline, concentrations VEGF-A (3698 ± 2105 pg/mL vs. 233 ± 98 pg/mL) and PEDF (18.9 ± 11.9 ug/mL vs. 2.2 ± 0.6 ug/mL) were higher (P < 0.001) in the study group (n = 20 patients) than control group (n = 20 patients). The VEGF-A/PEDF concentration ratio was higher in the study group (396 ± 554 vs. 110 ± 49; P = 0.02). One week after the ranibizumab injection, iris neovascularization had completely regressed in 17 (85%) eyes, and VEGF-A concentration decreased significantly (P < 0.001) to 184 ± 130 pg/mL. The PEDF concentration remained unchanged (19 ± 12 ug/mL). The VEGF-A/PEDF concentration ratio decreased to 13.2 ± 13.6. Plasma concentrations of VEGF-A and PEDF did not differ significantly between both groups (P = 0.65 and P = 0.15, respectively) nor were they significantly correlated with the aqueous concentrations (all P > 0.15). Conclusions: Aqueous concentrations of VEGF-A and PEDF were significantly elevated in eyes with neovascular glaucoma. Within one week after intravitreal injection of ranibizumab, VEGF-A concentration decreased to subnormal levels, while the PEDF concentration remained unchanged and the VEGF-A/PEDF ratio decreased.
Gesehen am 07.02.2018